A review of strategies to increase access to oral health services - Breyanna Davis; Sara Plaspohl (Georgia Southern University, 2017)
Background: Leading Health Indicators (LHIs), a subset of objectives for Healthy People 2020, were selected to communicate at-risk health issues and actions that can be taken to address them. Nationally, the number of children, adolescents, and adults who visited the dentist in the past year has decreased, suggesting that oral health continues to be a problem caused by barriers preventing access to oral health services. This review aimed to identify strategies to increase access to oral health services that will be useful in moving toward the LHI objectives. Methods: Preliminary research was conducted on the LHI via the Healthy People 2020 website. Health-related, peer-reviewed articles were selected and evaluated to determine current strategies used to increase access to oral health services that would lead to achievement of the LHI objectives. Results: Evidenced-based literature shows that economic, educational, and personal barriers prevent access to oral health services. Through health promotion and educational interventions, however, good oral health can be established. Such improvements will lead to attaining the LHI objectives in moving towards the target goals of Healthy People 2020. Conclusions: Since primary prevention and early intervention procedures lead to improved oral health, such methods can be useful in reaching the LHI objectives and the target goal of Healthy People 2020.